Male factor infertility with Azoospermia: our experience in a tertiary care centre - P., Sandeep Sethumadhavan; Sharma, Rajesh; Dhawan, Vikas; Chawla, Sushil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Azoospermia is the absence of spermatozoa in two separate centrifuged semen samples. It is one of the major contributors of male factor infertility. Usually detected in the course of infertility evaluation. Many forms of azoospermia are amenable to medical treatment. Authors report a case series of 16 cases of infertility with Azoospermia which were managed in the Assisted reproductive technology centre of a tertiary care teaching hospital of the Indian Navy in Mumbai between Jun 2022 to Jul 2023. Out of the 16 cases 13 cases underwent surgical sperm retrieval by PESA/TESE. We could retrieve sperms in 11 cases. In 5 cases the retrieved sperms were motile and in 6 cases immotile sperms were obtained. ICSI done with both motile and immotile sperms resulted in fertilization. Our study shows that IVF-ICSI can produce successful fertilization even with Immature sperms or sperms obtained directly from the testicular tissue and IVF-ICSI allows for pregnancy in couple where the man has irreversible azoospermia as long as it is possible to recover sperm from the testes.